Vanadium elicitation of Trifolium pratense L. cell culture and possible pathways of produced isoflavones transport across the plasma membrane - Kubes, Jan; Skalicky, Milan; Tumova, Lenka; Martin, Jan; Hejnak, Vaclav; Martinkova, Jaroslava (Plant cell reports, 2019)
Vanadium compounds increased the content and release of distinct isoflavones in a Trifolium pratense suspension culture. Regarding transport-mechanism inhibitors, the process was mostly facilitated by ABC proteins and vesicular transport. The transport of isoflavones and other secondary metabolites is an important part of metabolism within plants and cultures in vitro regarding their role in defence against various abiotic and biotic stressors. This research focuses on the way how to increase production and exudation of isoflavones by application of chemical elicitor and the basic identification of their transport mechanisms across cell membranes. The release of five isoflavones (genistin, genistein, biochanin A, daidzein, and formononetin) into a nutrient medium was determined in a Trifolium pratense var. DO-8 suspension culture after two vanadium compound treatments and cultivation for 24 and 48 h. The NH4VO3 solution caused a higher concentration of isoflavones in the medium after 24 h. This increased content of secondary metabolites was subsequently suppressed by distinct transport-mechanism inhibitors. The transport of isoflavones in T. pratense was mostly affected by ABC inhibitors from the multidrug-resistance-associated protein subfamily, but the genistein concentration in the medium was lower after treatment with multidrug-resistance protein subfamily inhibitors. Brefeldin A, which blocks vesicular transport, also decreased the concentration of some isoflavones in the nutrient medium.
Keywords: Biological Transport; buněčná membrána; biologický transport; Cell Membrane; Isoflavones; Vanadium; Red clover; Secondary metabolites; Abiotic elicitation; Plasma-membrane transport; isoflavony; vanad; Trifolium